Construction of a highly efficient CRISPR/Cas9-mediated duck enteritis virus-based vaccine against H5N1 avian influenza virus and duck Tembusu virus infection - Zhong Zou (Nature Portfolio, 2017)
Abstract Duck enteritis virus (DEV), duck tembusu virus (DTMUV), and highly pathogenic avian influenza virus (HPAIV) H5N1 are the most important viral pathogens in ducks, as they cause significant economic losses in the duck industry. Development of a novel vaccine simultaneously effective against these three viruses is the most economical method for reducing losses. In the present study, by utilizing a clustered regularly interspaced short palindromic repeats (CRISPR)/associated 9 (Cas9)-mediated gene editing strategy, we efficiently generated DEV recombinants (C-KCE-HA/PrM-E) that simultaneously encode the hemagglutinin (HA) gene of HPAIV H5N1 and pre-membrane proteins (PrM), as well as the envelope glycoprotein (E) gene of DTMUV, and its potential as a trivalent vaccine was also evaluated. Ducks immunized with C-KCE-HA/PrM-E enhanced both humoral and cell-mediated immune responses to H5N1 and DTMUV. Importantly, a single-dose of C-KCE-HA/PrM-E conferred solid protection against virulent H5N1, DTMUV, and DEV challenges. In conclusion, these results demonstrated for the first time that the CRISPR/Cas9 system can be applied for modification of the DEV genome rapidly and efficiently, and that recombinant C-KCE-HA/PrM-E can serve as a potential candidate trivalent vaccine to prevent H5N1, DTMUV, and DEV infections in ducks.